Serum Cytokine Concentrations in a Patient with Rheumatoid Arthritis on Etanercept Therapy Who Subsequently Developed Pneumocystis Pneumonia: A Case Report - Sato, Masao; Takemura, Masao; Shinohe, Ryuki; Shimizu, Katsuji (Case Reports in Rheumatology, 2011)
We report a rheumatoid arthritis patient who was treated with etanercept. Serum levels of tumor-necrosis-factor- (TNF-) alpha, soluble-tumor-necrosis-factor receptor- (sTNFR-) I and -II, interleukin- (IL-) 6, and IL-1 beta were measured by ELISA before and during the course of therapy. While the serum levels of IL-6 and IL-1 beta dropped rapidly following the initiation of therapy, the concentrations of TNF-alpha and sTNFR-II steadily increased to a plateau. Although significant clinical efficacy was observed, etanercept had to be discontinued when after 12 weeks of therapy the patient was found to have pneumocystis pneumonia.